Numerical Simulation of Fire Resistance Test for Gas Turbine Component Using Coupled CFD/FEM Approach - K. Y. Mokhov; A. Y. Kudryavtsev; O. V. Voronkov; E. B. Voronina; S. V. Sukhov; A. A. Ryabov; Y. N. Zhurenkov; A. V. Soloveva; A. V. Grigoriev (International Journal of Aerospace Engineering)
The article presents the implementation of CFD/FEM approach for real oil tank of the gas turbine engine for the purposes of prediction of the component behavior under the local impact of a burner jet. The model takes into account heat and mass transfer problems as well as strength problems that are solved using a one way coupled fluid-structure interaction method. Results of the blind test simulation are compared and show good agreement with available experimental data.